Functional Hybrid Nanoemulsions for Sumatriptan Intranasal Delivery - Ribeiro, Lígia N. M.; Rodrigues da Silva, Gustavo H.; Couto, Verônica M.; Castro, Simone R.; Breitkreitz, Márcia C.; Martinez, Carolina S.; Igartúa, Daniela E.; Prieto, Maria J.; de Paula, Eneida (Frontiers in Chemistry, 2020)
In the last years, advanced nanohybrid materials processed as pharmaceuticals have proved to be very advantageous. Triptans, such as the commercially available intranasal sumatriptan (SMT), are drugs employed in the treatment of migraine painful symptoms. However, SMT effectiveness is limited by its high hydrophilicity and poor mucoadhesion. Therefore, we designed hybrid nanoemulsions (NE) composed of copaiba oil as the organic component and biopolymers (xanthan, pectin, or alginate) as the continuous aqueous phase, aiming at the intranasal release of SMT (2% w/v). Firstly, drug-biopolymer complexes were optimized in order to decrease the hydrophilicity of SMT. The resultant complexes were further encapsulated in copaiba oil-based nanoparticles, forming NE formulations. Characterization by FTIR-ATR, DSC and TEM techniques exposed details on the molecular arrangement of the hybrid systems. The long-term stability of the hybrid NE at 25 °C was confirmed over a year, regarding size (~ 120 nm), polydispersity (~ 0.2), zeta potential (~ -25 mV), and nanoparticle concentration (~ 2x1014 particles/mL). SMT encapsulation efficiency in the formulations ranged from 41-69 %, extending the in vitro release time of SMT from 5 h (free drug) to more than 24 h. The alginate-based NE was selected as the most desirable system and its in vivo nanotoxicity was evaluated in zebrafish model. Hybrid NE treatment did not affect the spontaneous movement nor induced morphological changes in zebrafish larvae, with no evidences of mortality or cardiotoxicity, after 48 h of treatment. With these results, we propose alginate-based nanoemulsions as a potential treatment for migraine pain.